Enhancing the Lifetime and Corrosion Resistance of Gear Made of Carbon Steel - Ramlee, Ezwani (IRC, 2018)
Gears for structural machine require high fatigue strength for high performance. Generally, gears made of carbon steel worn and corroded easily thus the useful lifetime of the gears became short. This project aimed to increase the hardness and corrosion resistance of carbon steel gear by heat treatment method which was nitriding consisting of 95% nitrogen gas as well as 5% hydrogen gas and to investigate its properties after nitriding. In this project, gas nitriding process was chosen to be conducted to increase the hardness and corrosion resistance of gears at two different tube furnace temperatures: low (550°C) and high (1150°C), both for four hours. Microstructural and mechanical property evaluation of the low and high temperature nitrided low- carbon steel or also known as mild steel BS970-080A15 were studied and the results were compared to identify which gear has better performance in terms of hardness as well as corrosion resistance. From this experiment, the high-temperature nitrided carbon steel had improved its hardness by 113.18% which was from HV233.6 to HV498 in average compared to the raw carbon steel but in low temperature, the hardness only increased by 19.69%. Meanwhile, the corrosion rate of high-temperature nitrided carbon steel when compared to the raw material displayed a reduction of 56.67% from 0.1637 to 0.07095 millimeter per year while the corrosion rate in the low temperature reduced by 43.33%. The results from Vickers hardness test and weight loss analysis proved that high-temperature nitrided carbon steel was greater in hardness and corrosion resistance than the low-temperature nitrided carbon steel thus the lifetime and corrosion resistance of gears made of carbon steel were enhanced by nitriding.